Dinamika Komunikasi Antarpribadi dalam Keluarga Urban: Strategi Pencegahan Kenakalan Remaja di Era Digital - Putri Nur Azizah; Shinta Kristanty (Yayasan Literasi Sains Indonesia, 2025)
Teenagers in the digital era within urban families tend to use technology more intensively to obtain information. When parents are less active in communicating with their adolescents, this condition can contribute to juvenile delinquency. This study aims to analyze interpersonal communication between parents and adolescents in urban families in South Tangerang City as an effort to prevent juvenile delinquency in the digital era. Interpersonal communication is an approach that can be used to ensure harmonious communication between parents and adolescents. This study applies concepts of interpersonal communication, urban families, and juvenile delinquency in the digital era. The research employs a qualitative descriptive method with data collection techniques including interviews, observations, and literature studies. The study was conducted with six informants consisting of three mothers and three adolescents living in the Sawah Baru and Pondok Ranji sub-districts. The findings indicate that interpersonal communication between parents and adolescents is carried out through openness, empathy, support, positive attitudes, and equality. In this context, parents (mothers) strive to create a comfortable communication environment with their adolescents and also attempt to position themselves as friends. In interpersonal communication, parents carefully choose words and adjust to situations and conditions so that they can accompany their adolescents when using social media. As a result, information obtained from social media can be filtered by adolescents, thereby preventing juvenile delinquency in the digital era.